Chemical composition and insecticidal activity of volatile oils of Allium cepa bulb and Carica papaya leaf against Balanogastris kolae infestation on stored Kolanuts - Odeyemi, E.F.; Alabi, O.Y.; Olaoluwa, O.O.; Kpongbe, H.; Badmos, S.T.; Tamò, Manuele (2024)
This study investigated the phytochemicals present in the hexane extracts of red Allium cepa bulbs and Carica papaya leaves and the insecticidal activity of their essential oils against Balanogastris kolae. Saponins, flavonoids, tannins, alkaloids, phenols, and cardiac glycosides were found in the hexane extracts of A. cepa bulbs and C. papaya leaves. The GC-MS analysis of these essential oils showed that the most abundant compounds in A. cepa oil were the aromatic compounds, which was about 32% of the whole constituents, followed by about 26% organosulfur compounds. In the C. papaya leaf oil, β-Bisabolene (9.3201%), Linalool (2.0773%) and Limonene (1.6953 %) were prominent. The contact toxicity assay showed that the insecticidal activity of essential oil of C. papaya leaf were stronger than that of A. cepa bulb at lower concentrations because after 24 hours of exposure to treatments, percentage mortality of B. kolae was higher in C. papaya, ranging from 65.27 (5% concentration) to 87.50 (15% concentration) compared to that of A. cepa which ranged from 8.06 (10% concentration) to 73.31 (20% concentration). Both A. cepa and C. papaya oil have no fumigant property as there was no statistical difference in percentage mortality across all the treatments. Conclusion: C. papaya leaf and A. cepa bulb essential oils can be used as a bio-insecticide (contact toxicity) against B. kolae, as they compared favourably with synthetic insecticide, 2, 2 - Dimethyl dichloro vinyl phosphate (DDVP). This is the first report on the use of the essential oils of A. cepa bulbs and C. papaya leaf against Balanogastris kolae.